2021
DOI: 10.7759/cureus.20105
|View full text |Cite
|
Sign up to set email alerts
|

Scalpel Please! A Scoping Review Dissecting the Factors and Influences on Professional Identity Development of Trainees Within Surgical Programs

Abstract: Professional identity development is a multifaceted process that has recently sparked interest in medical education. Literature in professional identity development has focused predominantly on medical students and postgraduate medical training and much less on surgery, despite the unique challenges faced by surgical trainees while trying to emulate the identity of a self-actualized surgeon.A scoping review was performed to explore the factors and influences on professional identity development of surgeons in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…The majority of articles ( n = 21) utilised interview data, with the remaining three drawing on published life narratives and reflective journals. This reflects the state of qualitative professional identities research across other disciplines 7,14,37 . For example, a recent review of physician identities research identified that semi‐structured interview data prevails 14 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The majority of articles ( n = 21) utilised interview data, with the remaining three drawing on published life narratives and reflective journals. This reflects the state of qualitative professional identities research across other disciplines 7,14,37 . For example, a recent review of physician identities research identified that semi‐structured interview data prevails 14 .…”
Section: Discussionmentioning
confidence: 98%
“…There have been a number of reviews over the past decade synthesising the increasingly available empirical literature exploring a range of health care professional identities 2,5,7–15 . Much of the literature within these studies originates from the USA, Canada, the UK and Australia 2,7–10 .…”
Section: Reviews Of Professional Identity In Health Care Professions:...mentioning
confidence: 99%
See 2 more Smart Citations
“…A strong evidence base exists within and outside of neurosurgery demonstrating a correlation between clinical performance and objective assessment of surgeons' anatomical pro ciency. 38,39 Despite anatomy expertise representing an intrinsic aspect of the neurosurgical professional identity, [40][41][42] around a quarter of respondents stated they did not enjoy studying neuroanatomy and a smaller fraction believed that studying neuroanatomy was not relevant. It is unclear whether carrying these sentiments may impact learning and clinical performance.…”
Section: Neuroanatomy Studying Habits and Resourcesmentioning
confidence: 99%